Towards a better understanding of human smuggling - Heckmann, Friedrich (IMISCOE Policy Brief, 2007)
Contents: What is human smuggling?; How can we know about human smuggling?; Human smuggling as a migration phenomenon; Human smuggling as a business; The social organizing of human smuggling; Fighting against human smuggling.